2021
DOI: 10.3390/bios11100394
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy-Based Biosensors for MRD Detection and Treatment Monitoring in Non-Small Cell Lung Cancer (NSCLC)

Abstract: Globally, non-small cell lung cancer (NSCLC) is the leading cause of cancer deaths. Despite advancements in chemotherapy and targeted therapies, the 5-year survival rate has remained at 16% for the past forty years. Minimal residual disease (MRD) is described as the existence of either isolated tumour cells or circulating tumour cells in biological liquid of patients after removal of the primary tumour without any clinical signs of cancer. Recently, liquid biopsy has been promising as a non-invasive method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…[99][100][101] From a monitoring perspective, they allow for easy and frequent repeated testing and have been shown to be extremely useful for detection of minimal residual disease and risk of relapse. 102,103 The advent of 'personalised medicine' in which a patient's treatment is tailored towards their specific genetic or molecular profile has certainly been a key driver of the push for biomarker validation. Indeed, there are numerous examples of cancer biomarkers that are used to quantify the residual risk faced by patients and identify those groups of patients likely to benefit from costly, novel treatment approaches.…”
Section: Cancer Biomarkersmentioning
confidence: 99%
“…[99][100][101] From a monitoring perspective, they allow for easy and frequent repeated testing and have been shown to be extremely useful for detection of minimal residual disease and risk of relapse. 102,103 The advent of 'personalised medicine' in which a patient's treatment is tailored towards their specific genetic or molecular profile has certainly been a key driver of the push for biomarker validation. Indeed, there are numerous examples of cancer biomarkers that are used to quantify the residual risk faced by patients and identify those groups of patients likely to benefit from costly, novel treatment approaches.…”
Section: Cancer Biomarkersmentioning
confidence: 99%
“…With the progress of technology, the sensitivity of personalized gene sequencing technologies in tracking more mutations and thereby detecting low-volume MRD is gradually increasing. However, the clinical application of liquid biopsy is limited due to its operating cost ( 11 ). The obvious advantage of some non-blood-derived fluid biopsies is that the exfoliated tumor cells can be collected from the body fluids in direct contact with the tumor, ensuring the content of tumor markers and their correlation with the primary tumor.…”
Section: Advantages Of Non-blood-derived Fluid Biopsymentioning
confidence: 99%
“…In recent years, liquid biopsy has been introduced into clinical practice as a valuable tool for early diagnosis of recurrence and metastasis of non-small cell lung cancer (NSCLC) (8)(9)(10)(11)(12). Circulating tumor DNA (ctDNA) mainly comes from the small fragments of DNA released by apoptotic or necrotic tumor cells in tumor tissues into the blood system and the DNA released by the lysis of circulating tumor cells or micrometastases in the blood (13).…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used for early diagnosis, prognostic stratification, disease monitoring and treatment response assessment in different cancer types ( 14 16 ). Liquid biopsy techniques based on plasma ctDNA analysis can monitor and track personalized disease-related markers at the molecular level, and can be used to detect molecular residual desease (MRD) after treatment ( 10 , 17 , 18 ). In the TRACERx study, Addosh et al ( 19 ) found that ctDNA test after surgery could detect tumor recurrence or metastasis earlier than imaging.…”
Section: Introductionmentioning
confidence: 99%